2021
DOI: 10.3390/ijms221910219
|View full text |Cite
|
Sign up to set email alerts
|

Highlights on the Role of KRAS Mutations in Reshaping the Microenvironment of Pancreatic Adenocarcinoma

Abstract: The most frequent mutated oncogene family in the history of human cancer is the RAS gene family, including NRAS, HRAS, and, most importantly, KRAS. A hallmark of pancreatic cancer, recalcitrant cancer with a very low survival rate, is the prevalence of oncogenic mutations in the KRAS gene. Due to this fact, studying the function of KRAS and the impact of its mutations on the tumor microenvironment (TME) is a priority for understanding pancreatic cancer progression and designing novel therapeutic strategies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 95 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…With the application of monoclonal antibodies targeting programmed death 1 (PD-1) and its primary ligand PD-L1, the treatment paradigm for most advanced solid tumors has been fundamentally altered. Further studies have also been conducted in KRAS mutant tumors, and data shows that KRAS mutations may reshape the tumor immune microenvironment [ 62 ]. An analyzer powered by artificial intelligence based on hematoxylin and eosin showed that KRAS mutations were mostly found in the inflamed subtype of the immune microenvironment [ 63 ].…”
Section: Therapeutic Strategies In Kras-mutant Cancersmentioning
confidence: 99%
“…With the application of monoclonal antibodies targeting programmed death 1 (PD-1) and its primary ligand PD-L1, the treatment paradigm for most advanced solid tumors has been fundamentally altered. Further studies have also been conducted in KRAS mutant tumors, and data shows that KRAS mutations may reshape the tumor immune microenvironment [ 62 ]. An analyzer powered by artificial intelligence based on hematoxylin and eosin showed that KRAS mutations were mostly found in the inflamed subtype of the immune microenvironment [ 63 ].…”
Section: Therapeutic Strategies In Kras-mutant Cancersmentioning
confidence: 99%
“… 25 Activating KRAS mutations are the earliest and most common genetic alterations to occur in PDAC progression; they are present in greater than 90% of low‐grade PanINs and 90–95% of PDAC. 26 , 27 , 28 KRAS encodes a membrane‐bound GTPase that regulates a range of critical intracellular processes such as cell growth, differentiation, and survival by moving between its GDP‐bound inactive and GTP‐bound active form. 25 , 29 KRAS is usually present in quiescent cells in its inactive form; upon growth stimulation, guanine nucleotide exchange factors (GEFs) catalyze the GDP–GTP exchange to change KRAS into its active state.…”
Section: Current Understanding Of Pdacmentioning
confidence: 99%
“…This can result in the differentiation of CD4 + CD25 − cells into T regulatory (Treg) cells [ 7 ] and recruitment in colorectal cancer (CRC), PDAC and other cancers [ 8 ]. In addition, KRAS mutations induce growth factors such as interleukin-6 (IL-6) and IL-10, transforming growth factor-β (TGF-β) and sonic hedgehog (Shh) [ 9 ].…”
Section: Introduction-overview Of Genes Frequently Mutated In Pdacmentioning
confidence: 99%